A Feasibility study on the production of Powedered Carabao Milk - Nadal, Gemmalyn P.; Santos, Rowell; Serdoncillo, Guy. (Diliman, Quezon City College of Engineering, 2003)
The Philippine dairy market is primarily dependent on imported raw materials. The existing dairy industry in the Philippines is focused on processing and repackaging of imported products. This import dependence can be addressed with the establishment of a local manufacturer of powdered milk utilizing local raw materials. For the product to be distinct, carabao milk will be used as the raw material for the production of powdered milk. Its establishment will not only further the government's initiative in setting a local dairy enterprise and in promoting the carabao but also help improve the nutritional situation in the country. The first part of the study was to determine the market for Powdered Carabao Milk in the Philippines. Preliminary data from National Dairy Authority, National Statistics Office, Bureau of Agricultural Statistics and other agencies, which concerns the Philippine dairy industry, were gathered and analyzed. Research shows that comparison of properties between carabao and cow milk, the carabao-based milk was found to be more nutritious than the existing cow-based powdered milk in the market. The company will be named MilkLand Incorporated, which reflects the product it is going to produce. The product name, on the other hand, will be YOUR MILK this somehow resembles a form of ownership for the buyer though it has yet to compete with a highly competitive market. The demand analysis revealed an increasing trend on family expenditure for the powdered milk in the National Capital Region and in the Philippines as a whole based on the Family Income and Expenditure Survey conducted by the National Statistics Office. This trend is expected to occur over the years to come. On the other hand, the supply of powdered milk is highly dependent on imports as shown in the Philippine Dairy Update by the National Dairy Authority. This dependence on imported milk products represents a good opportunity for the establishment of a local milk powder manufacturing plant. A survey was conducted to determine the acceptability and potential market for the product. The target market of the product are the growing children ages 6 years old and above. From the survey, it was found that 66 percent of the respondents are willing to buy the product if it is available in the market. The survey also revealed that only 33 percent of the respondents have already tried the liquid carabao milk, this means that an extensive marketing strategy has to be developed to capture the target market. Three major milk industry players namely Nestle Philippines. Alaska Milk Corporation, and New Zealand Milk Philippines were also known to be the strong competitors of the company. Excellent marketing strategies were then developed to efficiently and effectively reach the target market. These strategies include having a brand name for the product, excellent packaging and labeling, offering the product in a variety of sizes, and integrating quality in the product. Sales promotions, product sampling in strategic areas, publicity through government agencies and feature stories, and advertising through newspapers, outdoor advertising, and television were evaluated and considered as part of the strategy. Proper distribution channels like personal selling and retailing were also employed. These strategies were designed to be extensive especially in the introductory year of the product to strongly penetrate the market. With these plans and strategies, the target share of 66 percent of the powdered milk sector can be recognized. A marketing budget was then developed to properly reflect the cost of the strategies the company will employ for the realization of its market goal, which is to capture a market that will justify its existence. The production of powdered whole milk requires technical analysis to find out whether the product can be properly manufactured, that is, it should be able to meet quality standards set by different agencies. With this, the different characteristics of the product were identified. From the market information for the demand of powdered milk, the capacity for the company was then established. It is expected that the company will employ a chase strategy, that is, the company will produce the required production output, which are basically the forecasted demands for each year. From here, it was planned that a 50,000 metric ton-design capacity for the five-operation of the company will be set. Based from this capacity, the different production requirements were established. These included machine and equipment, raw materials, and manpower requirements. The facility was designed to properly produce the product with the highest quality and at the same time meet the demands of the market. Site selection is done with three alternative sites known namely Bulacan, Laguna and Nueva Ecija. Bulacan was chosen as the site for the establishment of the company since it was able to meet all the criteria set by the company in its evaluation. A layout of the plant was designed using the relationship diagramming method that integrates the relationships among the different departments and activities in the plant. Carabao farming is a major aspect of the study since the company plans to have its own source of milk and also because there are no suppliers of liquid carabao milk that can sufficiently supply the requirements of the company. The costs of setting up the plant including buildings, manpower needed, and utilities were then evaluated. Financial analysis was then conducted to determine the financial viability of the project. Financial Statements; income statement, cash flow statement, balance sheets, for the five year operation of the company were developed. Financial ratio tests and sensitivity analysis show that the company is adequately liquid, profitable, and has a good earning power and the breakeven values are less than the expected sales of the company. The net present value was determined to be greater than zero and the internal rate of return was found to be 42.81%, greater than the minimum attractive rate of return of 18%. The results of the various areas of the financial analysis show that the project is financially viable. The social profitability of the company was also determined. Its contribution to the national economy and improvement in the standard of living of its employees were analyzed. Both the quantitative and qualitative aspects of the project revealed that its socio-economic contributions far outweigh its negative effects. It was then concluded that the establishment of powdered carabao milk manufacturing plant is socially and economically profitable. It can then be concluded that the establishment of a local powdered milk manufacturing plant is feasible.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management.
Keywords: MilkLand Philippines Incorporated; Dried milk industry; Dairy products industry; Participatory monitoring and evaluation (Project management)